New Therapeutic Approaches in Inflammatory Diseases of the Eye - Targeting Lymphangiogenesis and Cellular Immunity: Research Unit FOR 2240 Presents Itself - Cursiefen, Claus; Bock, Felix; Clahsen, Thomas; Regenfuss, Birgit; Reis, André; Steven, Philipp; Heindl, Ludwig M.; Bosch, Jacobus J.; Hos, Deniz; Eming, Sabine; Grajewski, Rafael; Heiligenhaus, Arnd; et al. (Klinische Monatsblätter für Augenheilkunde, 2017)
Background Ophthalmology, principally, is a very successful subdiscipline in medicine. Nonetheless, there are still unmet medical needs which necessitate translational research. Methods The funding instrument of a Research Unit (RU) of the German Research Foundation (DFG) is presented as exemplified by the RU 2240 at the Department of Ophthalmology at the University of Cologne. Results The Research Unit integrates different research groups working on pathologic ocular inflammation, macrophages/microglia and (lymph)angiogenesis to collaborate in a synergistic way. Rotation positions allow young clinicians to rotate into research labs for a defined period of time. A Research Unit is also a powerful strategic tool to strengthen clinical and experimental ophthalmology at individual medical faculties. Conclusions The funding instrument of a Research Unit is highly suitable for fostering translational research in a medical subdiscipline such as ophthalmology, supporting the next generation of (clinician) scientists in ophthalmology and finding new cures for our patients.
EVALuna2:9372